Dampak Kebijakan Penanganan Pandemi Covid 19 Berdasarkan Persepsi Masyarakat Kota Lama Semarang Sebagai Ruang Terbuka Publik - Tefi Liring Aditya; Grandy Loranessa Wungo (Jurusan Perencanaan Wilayah dan Kota, 2023)
The goal to be achieved in this study is to find out how the public's perception of the implementation of the Covid 19 pandemic handling policy in the Kota Lama Semarang as a public space. That will be done by analyzing how the perception of people who are active in the Old City of Semarang after the pandemic handling policy in the Kota Lama Semarang As a public space the research method that will be used in this study is quantitative and qualitative methods, using descriptive analysis and scoring and weighting analysis. Data collection techniques used were questionnaires and interviews with community respondents who visited the Kota Lama Semarang.The results of this study are the results of an analysis that has been carried out in the aspect of an ideal public open space consisting of Comfort, Activities, Accessibility and Sociability which were selected based on the book Public Space by Stepher Carr and Public Space & Urban Spaces by Carmona, which was then carried out after scoring analysis. and supported by the interview results obtained very good results which show that the Kota Lama Semarang has been able to adapt to the existing pandemic conditions.